THE EFFECT OF THE IODINE-CONTAINING COMPOUNDS ON GENE EXPRESSION OF PATHOGENIC MICROORGANISMS - Kenesheva, S.T.; Jumagaziyeva, A.B.; Turganbay, S.; Iskakbayeva, Zh. A.; Jumabayeva, S.M.; Zhaumitbayeva, G.A.; Ilin, A.I.; Azembayev, A.A. (Eurasian Journal of Applied Biotechnology, 2024)
The global increase in multidrug resistance highlights the need for new, effective antimicrobial agents. Iodine-containing complexes, due to their broad-spectrum antimicrobial properties, low likelihood of resistance development, and stability under various conditions, represent a promising avenue for the development of innovative therapeutic approaches. The aim of this study was to collect and analyze research assessing the impact of iodine-containing complexes with organic ligands on the gene expression of certain pathogenic strains of microorganisms with multidrug resistance. Bioinformatics approaches were employed to investigate gene expression, protein interactions, and metabolic pathways, utilizing tools like STRING, KEGG, Reactome, and UniProt. Models of gene and proteome interaction analysis were also used to interpret the data. Key findings include the suppression of central metabolic cycles, such as the tricarboxylic acid cycle (TCA), increased glycolytic activity, a shift in metabolism toward anaerobic respiration, and activation of oxidative stress defense systems. The study also highlights changes in gene expression associated with membrane remodeling, DNA repair, regulation of virulence factors, and nutrient transport. These adaptive responses reflect the multifaceted antimicrobial action of iodine-containing complexes, which target key cellular components and processes, making them highly effective against multidrug-resistant pathogens. Iodine-containing complexes exhibit high antimicrobial potential due to their ability to disrupt essential bacterial life processes, impairing metabolism, structure, and adaptive mechanisms. Further research into the molecular mechanisms of iodine’s action and its effects on pathogen virulence could open new avenues for addressing the challenge of antibiotic resistance.